(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Over the years , Information System has advanced so much that we are able to operate better in an organization which is better than what used to happen in the past. Information Systems derived from the term data processing. The purpose of Information Systems is to provide efficient and reliable ways on how to perform functions in an organization. Computers have important role in evolution of Information System. There have been a lot of applications of Information System in the organizations today including human resource operation as the main field of concern, accounting andÂ finance, logistics and planning among others. Internet is the recent development in the use of Information.Â Studies have been carried out on Information System and its application but none of the studies have looked at the role Information System plays in typical organizational operational functions especially in the Human Resource Operations. This therefore leaves the gap in research that this paper sought to breach. The study is conducted through analysis of literature review from journals, and surveys. The paper therefore recommends that organizations should apply Information Systems in Human Resources operationsÂ in order to reap these benefits.